A qualitative study on the effects of teacher attrition - Wushishi, Aminu Aliyu; Foo, Say Fooi; Basri, Ramli; Baki, Roslen (Australian International Academic Centre, 2014)
In this study the researchers explored the effects of teacher attrition in Niger state, Nigeria. The study examined how attrition is affecting the educational development of the state from the teachers’ perspective. A qualitative method was used with the aim of extracting the inner feelings of the participants regarding the effects of attrition. Five serving teachers were purposively selected. An in-depth interview, non-participatory observation and document analysis were used as means for data collection. The findings discovered; cost implication, increased in workload, poor students’ performance and burden on school administration, as the major effects of teacher attrition. The paper therefore recommends that, the state government needs to improve the condition of service of teachers with the aim of reducing the rate of attrition so as to improve the educational standard of the state.